A portable magneto-optical trap with prospects for atom interferometry in civil engineering. (6th August 2017) - Hinton, A.; Perea-Ortiz, M.; Winch, J.; Briggs, J.; Freer, S.; Moustoukas, D.; Powell-Gill, S.; Squire, C.; Lamb, A.; Rammeloo, C.; Stray, B.; Voulazeris, G.; et al.
Abstract : The high precision and scalable technology offered by atom interferometry has the opportunity to profoundly affect gravity surveys, enabling the detection of features of either smaller size or greater depth. While such systems are already starting to enter into the commercial market, significant reductions are required in order to reach the size, weight and power of conventional devices. In this article, the potential for atom interferometry based gravimetry is assessed, suggesting that the key opportunity resides within the development of gravity gradiometry sensors to enable drastic improvements in measurement time. To push forward in realizing more compact systems, techniques have been pursued to realize a highly portable magneto-optical trap system, which represents the core package of an atom interferometry system. This can create clouds of 10 7 atoms within a system package of 20 l and 10 kg, consuming 80 W of power. This article is part of the themed issue 'Quantum technology for the 21st century'.